2021
DOI: 10.1177/19322968211043498
|View full text |Cite
|
Sign up to set email alerts
|

Six Digital Health Technologies That Will Transform Diabetes

Abstract: The digital health revolution is transforming the landscape of medicine through innovations in sensor data, software, and wireless communication tools. As one of the most prevalent chronic diseases in the United States, diabetes is particularly impactful as a model disease for which to apply innovation. As with any other newly developed technologies, there are three key questions to consider: 1) How can the technology benefit people with diabetes?, 2) What barriers must be overcome to further advance the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Findings from this study are in line with recent literature demonstrating the acceptability and benefits of telehealth-based delivery of diabetes care, which is increasingly becoming a recommended avenue to increase access to care, increase frequency of visits while minimizing travel and time burden, and to monitor patients remotely between visits. [19][20][21][22] The SARS-CoV-2 pandemic led to a rapid acceleration of expanding the use of telehealth-based care 23,24 and highlighted its potential as major paradigm shift in diabetes care 25,26 as well as some challenges (e.g., risk of widening disparities and gaps in access particularly with rural populations; concern about less personalized care over time; lower rates of anthropometric and lab measurements). [27][28][29] Recent research has demonstrated that most patients and providers have been satisfied with telehealth-based diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study are in line with recent literature demonstrating the acceptability and benefits of telehealth-based delivery of diabetes care, which is increasingly becoming a recommended avenue to increase access to care, increase frequency of visits while minimizing travel and time burden, and to monitor patients remotely between visits. [19][20][21][22] The SARS-CoV-2 pandemic led to a rapid acceleration of expanding the use of telehealth-based care 23,24 and highlighted its potential as major paradigm shift in diabetes care 25,26 as well as some challenges (e.g., risk of widening disparities and gaps in access particularly with rural populations; concern about less personalized care over time; lower rates of anthropometric and lab measurements). [27][28][29] Recent research has demonstrated that most patients and providers have been satisfied with telehealth-based diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…2 This data can be collected, transmitted, presented, stored, and processed in real time to be used in decision support software or algorithms for an HCP to review in real time or asynchronously. 3 To be most useful, the data must integrate into a patient’s electronic health record (EHR). 4…”
Section: Introductionmentioning
confidence: 99%
“…2 This data can be collected, transmitted, presented, stored, and processed in real time to be used in decision support software or algorithms for an HCP to review in real time or asynchronously. 3 To be most useful, the data must integrate into a patient's electronic health record (EHR). 4 Currently, very few healthcare organizations (HCOs) have successfully integrated continuous glucose monitor (CGM) data directly into the EHR, and most of those have done so with the assistance of third-party integration engines or data aggregators.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the known physiologic responses to a low blood glucose level, this novel approach could be used to qualitatively and accurately detect the onset of clinically significant hypoglycemia. 2 We commend Dave and colleagues for their work. However, we would like to point out two additional factors to consider in any discussion of technology for qualitative detection of hypoglycemia.…”
mentioning
confidence: 99%
“…Finally, we believe that greater accuracy of hypoglycemia detection can be achieved through incorporating multiple data streams into an aggregate multiple sensor-data platform, 2 rather than relying on information from a single sensor. Dave et al created their model by modifying ECG data with contextual information provided by an accelerometry sensor.…”
mentioning
confidence: 99%